2012
DOI: 10.1890/11-0458.1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of deer management on the abundance of Ixodes ricinus in Scotland

Abstract: The management of wildlife hosts for controlling parasites and disease has a history of mixed success. Deer can be important hosts for ticks, such as Ixodes ricinus, which is the primary vector of disease-causing zoonotic pathogens in Europe. Deer are generally managed by culling and fencing for forestry protection, habitat conservation, and commercial hunting, and in this study we test whether these deer management methods can be useful for controlling ticks, with implications for tick-borne pathogens. At dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
135
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(153 citation statements)
references
References 44 publications
14
135
4
Order By: Relevance
“…Our findings agree with Gilbert et al 38 , who found a strong decrease in the density of I. ricinus nymphs in both large and small (<1 ha) exclosures. However, they disagree with a meta-analysis by Perkins et al 194 who found that exclosures >2.5 ha were needed to reduce densities of I. scapularis and Amblyomma americanum.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our findings agree with Gilbert et al 38 , who found a strong decrease in the density of I. ricinus nymphs in both large and small (<1 ha) exclosures. However, they disagree with a meta-analysis by Perkins et al 194 who found that exclosures >2.5 ha were needed to reduce densities of I. scapularis and Amblyomma americanum.…”
Section: Discussionsupporting
confidence: 93%
“…Van Buskirk and Ostfeld 27 , for example, modelled how nymph densities of I. scapularis responded to differences in densities of hosts for larvae and adults, and found that the density of hosts for adults was limiting nymph density only at very low host densities, where the availability of hosts for larvae then became limiting. Thus, nymph and adult density appear related to deer density according to a nonlinear threshold relationship, rather than the linear relationship used in most studies (e.g., Gilbert et al 38 and Sprong et al 39 ). Furthermore, Van Buskirk and Ostfeld 27 suggested that the threshold adult-host density is close to zero.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations